Genotyping of angiotensin-1 converting enzyme insertion/deletion gene polymorphism in malay ischemic stroke patients - Pei, Cheung Tian (Universiti Sains Malaysia, 2012)
The human angiotensin-1 converting enzyme (ACE) gene contains an insertion or deletion (I/D) of Alu repeat element in intron 16 of the chromosome 17 (17q23). This polymorphism has been widely investigated to determine its effects in causing ischemic stroke but inconsistent results are obtained. Thus, this study aims to genotype the ACE I/D polymorphism to determine its genotypic frequency among Malay ischemic stroke patients. The study subjects comprised of 27 Malay ischemic stroke patients that were recruited from HUSM. ACE I/D gene polymorphism was determined by genotyping the SNP rs4341 polymorphism using PCR-RFLP method. The frequencies of ACE polymorphism (II, ID and DD genotypes) were determined and presented in the form of percentage. The results showed that ACE II genotype was present in all Malay ischemic stroke patients (100%) while ID and DD genotypes did not make any contribution to the genotypic frequency. Therefore, the ACE II genotype is responsible for the occurrence of ischemic stroke among Malay stroke patients. However, the result is a preliminary finding in which larger and extensive studies can be performed based on it.